The meaning and legal consequences of ‘sole-trustee’ of waqf under the shariah and Malaysian waqf laws - Syed Abdul Kader, Sharifah Zubaidah; Mohamad, Nor Asiah; Ali, Zuraidah; Ishola, Abdullahi Saliu (2017)
All the laws relating to waqf in Malaysia contain a provision that make the State Islamic Religious Council as ‘sole trustee’ of all waqf properties in their respective states. This effectively makes the State Islamic Religious Council as the sole waqf authority for the state. Problems have arisen in regard to the scope of powers of the State Islamic Religious Councils in exercising their powers as ‘sole trustee’ for waqf in Malaysia. With the aim of minimising these problems and seeking legal solutions, this paper examines the meaning and legal consequences arising from the term ‘sole trustee’ in the context of waqf laws in Malaysia. It traces the rationale for inclusion of such provision and identifies some anomalies arising therefrom. This study adopts the doctrinal legal research method and uses primary legal sources such as statutes and decided cases as well as content analysis of the shariah sources to extract the meaning and legal and the shariah consequences of the term. It discusses the concepts of Nazir, Mutawalli and Qayyim under the shariah, examines issues relating to delegation of powers, appointment of waqf managers, the function and duties of waqf managers, and identifies issues arising from decided cases. Findings will provide direction for the waqf authorities to act and strategize for waqf management and development in accordance with the parameters of the shariah and the law. Keywords: waqf, waqf administration, sole-trustee, mutawalli